Evaluation of the Maqāṣid al-Sharī’ah Liberalization: An Examination of the Notion of ‘Prioritizing Public Interest over Textual Evidence’ - Sunaryo, Agus; Fahmi, Ahmad Hadidul (Al-Manahij: Jurnal Kajian Hukum Islam, 2024)
The effort to reconstruct Islamic law from liberal Muslim groups has a positive influence and acceptance for some people. However, the majority of Muslims have not been able to accept and prefer to follow the mindset and methodology of previous scholars. The concept of maqāṣid al-sharī’ah of liberal Muslim thinkers is methodologically considered not to have a strong basis because it dares to ignore the legal provisions in the specific daily, which are considered not in line with the purpose of the law and the benefit. Maqasid al-shari'ah should be built on efforts to integrate the texts of particular propositions into the texts of universal propositions (kully) so that the purpose of legal legislation can be understood. This article critically examines the concept of maqāṣid al-sharī’ah developed by liberal Muslim thinkers, especially in Indonesia. This study explicitly emphasizes the importance of Islamic law in realizing the benefits and being a solution to various problems of contemporary life. The benefit to be achieved is the ultimate and universal benefit, namely the benefit obtained through legal formulation efforts by making specific texts as a foothold to understand the purpose of the law. It is not an assumptive benefit (mawhūmah) obtained through legal reconstruction efforts based on the purpose of the law and the benefit but ignores the texts of particular arguments.